On Generalizations of Projective QTAG-Modules - Fahad Sikander; Firdhousi Begam; Tanveer Fatima (Journal of Mathematics)
In this manuscript, we define the class of ω1-weakly α-projective QTAG-modules for the infinite ordinal α and provide its systematic study for the finite ordinal. Furthermore, we generalize this class to ω.2+n-projective modules and obtain some characterizations. We also study the ω-totally weak ω.2+n-projective modules under the formation of ω1-bijections.